Occurrence of Foodborne Agents at Food Service Facilities in the Czech Republic - Bogdanovičová, Kateřina; Kameník, Josef; Dorotíková, Kateřina; Strejček, Jan; Křepelová, Simona; Dušková, Marta; Haruštiaková, Danka (Journal of food protection, 2019)
Contamination of food service facilities in the Czech Republic by foodborne agents was determined. Bacillus cereus, Staphylococcus aureus, and Escherichia coli were detected in almost 50% of samples. The occurrence of B. cereus, S. aureus, and E. coli depended on the season of the year. Regular monitoring of food service facilities for agents of foodborne disease is necessary.
Keywords: Food Microbiology; Shiga toxigenic; Česká republika; Staphylococcus aureus; stravovací služby; potravinářská mikrobiologie; Foodborne Diseases; Bacillus cereus; nemoci přenášené potravou; Bacteria; Escherichia coli; Czech Republic; spp; spp.; Food Services